Stem cell transplantation in neurodegenerative disorders of the gastrointestinal tract: future or fiction?. Issue 4 (4th August 2011) - Kulkarni, Subhash; Becker, Laren; Pasricha, Pankaj Jay
Abstract : Current advances in our understanding of stem and precursor cell biology and in the protocols of stem cell isolation and transplantation have opened up the possibility of transplanting neural stem cells for the treatment of gastrointestinal motility disorders. This review summarises the current status of research in this field, identifies the major gaps in our knowledge and discusses the potential opportunities and hurdles for clinical application.